Effects of Aging on Parasite Biomass, Inflammation, Endothelial Activation, Microvascular Dysfunction and Disease Severity in Plasmodium knowlesi and Plasmodium falciparum Malaria. (19th June 2017) - Barber, Bridget E.; Grigg, Matthew J.; William, Timothy; Piera, Kim A.; Boyle, Michelle J.; Yeo, Tsin W.; Anstey, Nicholas M.
Summary: In populations pauci-immune to malaria, risk of severe malaria increases with age. In knowlesi malaria, systemic inflammation, endothelial activation, and microvascular dysfunction increase with age, independent of parasitemia, and may account for the greater severity of disease seen in older adults. Abstract: Background: In populations pauci-immune to malaria, risk of severe malaria increases with age. This is particularly apparent in Plasmodium knowlesi malaria. However, pathophysiological mechanisms underlying knowlesi malaria, and of the age-related increase in risk of severe malaria in general, are poorly understood. Methods: In Malaysian patients aged ≥12 years with severe (n = 47) and nonsevere (n = 99) knowlesi malaria, severe (n = 21) and nonsevere (n = 109) falciparum malaria, and healthy controls (n = 50), we measured parasite biomass, systemic inflammation (interleukin 6 [IL-6]), endothelial activation (angiopoietin-2), and microvascular function, and evaluated the effects of age. Results: Plasmodium knowlesi parasitemia correlated with age (Spearman's correlation coefficient [ r s ] = 0.36; P < .0001). In knowlesi malaria, IL-6, angiopoietin-2, and microvascular dysfunction were increased in severe compared to nonsevere disease, and all correlated with age, independent of parasitemia. In falciparum malaria, angiopoietin-2 increased with age, independent of parasite biomass (histidine-rich protein 2 [HRP2]). Independent risk factors for severe malaria included parasitemia and angiopoietin-2 in knowlesi malaria, and HRP2, angiopoietin-2, and microvascular dysfunction in falciparum malaria. Conclusions: Parasite biomass, endothelial activation, and microvascular dysfunction are associated with severe disease in knowlesi malaria and likely contribute to pathogenesis. The association of each of these processes with aging may account for the greater severity of malaria observed in older adults in low-endemic regions.